Developing high safety Li-metal anodes for future high-energy Li-metal batteries: strategies and perspectives. (13th July 2020) - Liu, Dai-Huo; Bai, Zhengyu; Li, Matthew; Yu, Aiping; Luo, Dan; Liu, Wenwen; Yang, Lin; Lu, Jun; Amine, Khalil; Chen, Zhongwei
Abstract : Developing high-safety Li-metal anodes (LMAs) are extremely important for the application of high-energy Li-metal batteries. The recently state-of-the-art technologies, strategies and perspectives for developing LMAs are comprehensively summarized in this review. Abstract : Developing high-safety Li-metal anodes (LMAs) is extremely important for the application of high-energy Li-metal batteries (LMBs), especially Li–S and Li–O2 battery systems. However, the notorious Li-dendrite growth problem results in serious safety concerns for any energy storage application. Through a recent combination of interface-based science, nanotechnology-based solutions and characterization methods, the LMA is now primed for a technological boom. In this review, the recent emerging strategies and perspectives on LMAs are summarized, following which the current huge evolution in interfacial chemistry regulation, optimizing electrolyte components, designing a rational 'host' for lithium metal, optimizing "solid-state electrolytes" and other emerging strategies for developing high-safety LMAs is highlighted. Furthermore, several state-of-the-art in situ / operando synchrotron-based X-ray techniques for high safety LMB research are introduced. With the further development of LMAs in the future, subsequent application in high energy LMBs is to be expected.